Vegetation cover of the Kulaly Islands in the Kazakhstan region of the Caspian Sea - Sagyndykova, M.; Gasanova, G.; Imanbayeva, A.; Orazov, A. (Fundamental and Experimental Biology, 2025)
This study presents a comprehensive analysis of the floristic and ecological diversity of vascular plants on Kulaly Island, located in the Kazakhstani sector of the Caspian Sea. Field surveys documented 149 species, predominantly annual therophytes (47.0%) and perennial xerophytes, reflecting adaptations to arid climates, high soil salinity, and unstable substrates. Most taxa are associated with sandy and solonchak habitats, while wetland and aquatic ecosystems support comparatively fewer species. A quantitative assessment of alpha diversity using the Shannon (H′ = 1.55), Simpson (D = 0.71), and Pielou (J = 0.79) indices revealed a relatively high level of structural heterogeneity, with a balanced distribution of ecological groups. Canonical Correspondence Analysis (CCA) identified salinity, moisture, and substrate mobility as the primary environmental gradients structuring vegetation, with clear separation of halophytic, psammophytic, and hydrophilic communities. These findings demonstrate both the ecological plasticity of the flora and the vulnerability of rare and localised taxa to hydrological fluctuations of the Caspian Sea and anthropogenic pressures. The results provide a crucial scientific foundation for biodiversity monitoring, the conservation of genetic resources, and the sustainable management of fragile arid ecosystems in western Kazakhstan.